"YOU CAN’T SEE IT BUT IT’S A MATTER OF LIFE AND DEATH". OF PLATFORMS, POWER, AND THE INVISIBLE - Vicari, Stefania (AoIR Selected Papers of Internet Research, 2023)
We investigate the interplay of platform mechanisms and user tinkering in relation to invisible health conditions and ultimately challenge approaches that picture platforms as either hegemonic or liberating. We draw on initial findings from a project focused on social media uses relevant to hereditary cancer syndromes. These conditions are invisible in at least three ways. Cancer genetic risk is evidence-based and embodied, but not bodily visible. General health practitioners rarely know about hereditary cancer syndromes. Overall, hereditary cancer syndromes have not yet entered the wider collective imagination. Existing research provides evidence that individuals with these conditions turn to social media to seek, learn, produce and share information. However, little do we know about how these practices form at the intersection of embodied experiences, everyday social media uses, and platform mechanisms. In this paper we explore these dynamics drawing on a social media analysis that incorporates data from Twitter, Facebook, TikTok, and Instagram and combines computational and ethnographic techniques. When it comes to invisible health conditions, the voice of ordinary social media users easily overcomes that of traditional elites. Local platform mechanisms differently shape how information is shared and who and what become more visible and credentialed in these sharing practices. They also influence how and which personal experiences are more curated and shared. These initial findings suggest that social media platforms are essential in making the invisible visible but raise questions on how participating in one or more platforms’ “local worlds” might affect the lived experience of those who embody this invisible.